Menstruation Discrimination and the Problem of Shadow Precedents - Widiss, Deborah A. (Columbia Journal of Gender and Law, 2021)
The burgeoning menstrual justice movement highlights that women, girls, transgender men and boys, and non-binary persons may face discrimination or harassment due to their menstruation in workplaces, schools, prisons, and many other aspects of life. In recent years, a few courts have suggested such discrimination may violate Title VII, the federal law that prohibits sex discrimination in employment. Their analysis focuses on the Pregnancy Discrimination Act (PDA), an amendment to Title VII passed in response to a Supreme Court case holding that pregnancy discrimination was not sex discrimination. The PDA overrode the decision by explicitly defining sex as including “pregnancy, childbirth, or related medical conditions.” The menstruation discrimination cases thus implicate more general questions of how statutory overrides should be interpreted, a subject I’ve explored extensively in prior work. My research suggests that this nascent litigation campaign may face two distinct challenges. The first is that courts will simply deny the claims, reasoning that menstruation is not directly addressed by the text of the PDA and therefore should not be recognized as sex discrimination. The second—which is more subtle, and also perhaps more likely—is that courts could find such discrimination to be actionable, but do so relying solely on the PDA’s explicit reference to “medical conditions” related to pregnancy. While that would be helpful for addressing discrimination in workplaces, it could open the door to arguments that menstruation is outside the ambit of sex discrimination laws that were not amended in a manner analogous to how Title VII was amended. To avoid these potential risks, theorists and advocates should seek to establish that menstruation discrimination is discrimination on the basis of “sex” itself, in that it is a condition linked to female reproductive organs and associated with stereotypes about women’s inferiority. That reasoning, which suggests that the PDA is properly interpreted as signaling Congress’s disapproval with the Supreme Court’s unduly narrow understanding of what constitutes sex discrimination in the earlier pregnancy case, should apply not only to Title VII, but also to the interpretation of statutory and regulatory prohibitions on sex discrimination in non-employment contexts.